Repercussions of pneumoperitoneum for laparoscopic cholecystectomy on mechanical power with volume-controlled ventilation - Claudio Luciano Franck; Letícia Lopes Machado; Felipe Lopes de Moraes Pironatto; Rodrigo Soares (Journal of Mechanical Ventilation)
Background